Attention to diversity in compulsory secondary education: the professional’ perspectives - Liesa Hernández, Eva; Castelló, Montserrat; Carretero Torres, Mª Reyes; Cano, Maribel; Mayoral, Paula (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The aim of this research is to analyze the evolution of attention to diversity in Catalonia in the last decade on the basis of the opinions of different professionals in the world of education. The research, of a qualitative nature, was designed as a case study. Respondents were selected for their particular link to the Catalan educational system. Results show that the policies to make possible a model of inclusive schools have not been introduced clearly and resolutely. Likewise, a clear will to promote a school where everyone can work together has not been created among teachers. The way towards educational inclusion is long and requires different professional profiles to work together in the creation of a network of support and resources to facilitate quality schooling.